Extra note of music in anaesthesia - Kaur, Harpreet; Shukla, Veena; Bansal, Gopal Lal; Harsh, Harsh Kumar; Joseph, Anie; Bharadwaj, Meghana S. (International Journal of Research in Medical Sciences, 2019)
Role of music has been identified since ancient times for alleviating anxiety. Music has been known for its potential to produce a sense of wellbeing and peace. Anaesthesia and surgery are major stress factors for any person. Preoperative anxiety is a usual phenomenon in patients posted for various surgical interventions as well as those admitted to intensive care units (ICU). Literature shows ample evidence regarding neurohormonal disturbances related to stressful situations like preoperative, intraoperative and post-operative periods. Music has been shown to attenuate release of various biochemical molecules leading to relaxing and sedative effects on the brain. Not only patients under regional anaesthesia who are awake have a positive impact, even patients under general anaesthesia have also been shown to benefit from listening to music intraoperatively. Music is a hazard free intervention which can be added to various drug combinations used by anaesthesiologists.